Mechanistic insights into cadmium-related premature aging in Drosophila model - Maria Dolores De Donno; Ester Mercuri; Barbara Balena; Francesco Zangaro; Maria Pia Bozzetti; Valeria Specchia (Frontiers in Neuroscience)
The intricate and multifaceted relationship between environmental pollutants, particularly heavy metals such as cadmium, and human health has been extensively documented, with a significant focus on their neurotoxic effects. Notably, the connection between cadmium exposure and Alzheimer’s disease is becoming increasingly evident, prompting a deeper investigation into the underlying mechanisms at play. Despite the growing body of evidence linking cadmium to neurodegeneration and although harmful molecular activities of cadmium in cells have been demonstrated, the precise molecular mechanism induced by this toxic metal within neuronal cells remains largely enigmatic. This study aims to shed light on these mechanistic processes by utilizing Drosophila melanogaster, a widely recognized model organism in neurogenetics, as our experimental framework. Through a carefully designed approach, we simulated chronic exposure to cadmium, which allowed us to observe the resulting effects on the flies over time. Our findings revealed that chronic cadmium exposure led to premature aging in flies, characterized by neurodegeneration and an exacerbation of complex neurological phenotypes. Notably, these included significant impairments in learning and memory, which are critical cognitive functions often compromised in neurodegenerative conditions. With the aim of exploring the mechanistic underpinnings of these observations, we determined that cadmium impairs RNP formation and could disrupt the delicate process of liquid–liquid phase separation within neuronal cells. This disruption appears to play a pivotal role in initiating the cascade of events that contribute to neurodegeneration. Liquid–liquid phase separation is essential for the proper organization of cellular components and the maintenance of neuronal health; thus, cadmium’s interference in this process may provide a crucial insight into its neurotoxic effects.